The characteristics and determinants of capital structure in SME: empirical evidence from U.S. companies - Wu, Chia-Ying (2011)
Abstract This study investigates the determinants of capital structure of small and medium size enterprises (SMEs) in U.S. by using a panel data consisting of 100 firms from 2002 to 2010. In order to examine the financial crisis effects on SMEs’ gearing decision, the research period is divided into two time frames: pre-crisis (2002-2007) and post-crisis (2008-2010). Using the Fixed Effect Model through STATA software, the seven variables including profitability, firm size, firm age, tangibility, earnings volatility, non-debt tax shield and growth opportunity are tested against the short-term debt and the long-term debt. The evidence suggests that profitability and size are significant determinants for both short-term and long-term debt structure of the firm. Growth opportunity and non-debt tax shield have significant influence on long-term debt decisions. The other variables such as tangibility, age and earnings volatility do not contribute significantly to the SMEs’ capital structure. Furthermore, it is observed that financial crisis have considerable impacts on U.S. small firms as the average values of most of the proxies of the determinants are reducing after 2008.